Brief overview of VANET routing protocols and their security attacks (International Journal of Engineering and Computer Science, 2014)
We know that opinion a VANET specialized form of MANET. As we know that a VANET stands for vehicular ADHOC network. a VANET uses every participating car into a wireless node or router ,allowing cars approximately 100 to 300  meters of each other to connect and to form a network with wide range. as car falls out of the signal range ,other cars can join in, connecting vehicles to one other so that a mobile internet is created. However in this research paper I concentrate on classification of VANETS and their security attacks